Disease-Specific Anxiety in Chronic Obstructive Pulmonary Disease: Translation and Initial Validation of a Questionnaire - Farver-Vestergaard, Ingeborg; Rubio-Rask, Sandra; Timm, Signe; Christiansen, Camilla Fischer; Hilberg, Ole; Løkke, Anders (Frontiers in Psychology, 2022)
Background: Commonly applied measures of symptoms of anxiety are not sensitive to disease-specific anxiety in patients with chronic obstructive pulmonary disease (COPD). There is a need for validated instruments measuring COPD-specific anxiety. Therefore, we translated the COPD-Anxiety Questionnaire (CAF) into Danish (CAF-R-DK) and performed an initial validation of the psychometric properties in a sample of patients with COPD. Methods: Translation procedures followed the World Health Organization guidelines. Participants with COPD completed questionnaires measuring COPD-specific anxiety (CAF-R-DK), general psychological distress (Hospital Anxiety and Depression Scale) as well as variables related to COPD (COPD Assessment Test; modified Medical Research Council dyspnea scale), quality of life (the 12-item Short Form survey, SF12), and socio-demography. Results: A total of 260 patients with COPD (mean age: 65.0, 69% female) completed questionnaires. The Danish version of CAF-R-DK demonstrated acceptable Cronbach’s α values that were comparable with those of the original CAF. As expected, the CAF-R-DK showed positive correlations with convergent constructs (CAT; HADS) and negative correlations with discriminant constructs (SF-12). However, the results for specific subdomains of the CAF-R-DK indicated inconsistency in the underlying concept of disease-specific anxiety, which was also suggested based on the subsequent confirmatory and exploratory factor analyses. Conclusions: The CAF could serve as an important supplement to generic psychological distress screening of patients with COPD in somatic health care settings, and the questionnaire is now available in Danish. Translation into other languages is needed with the purpose of obtaining data for further testing the psychometric properties of the questionnaire.